2017
DOI: 10.1007/s11250-017-1283-y
|View full text |Cite
|
Sign up to set email alerts
|

Equine colic: clinical epidemiology and associated risk factors in and around Debre Zeit

Abstract: A prospective study was conducted to describe clinical epidemiology of equine colic in the Society for Protection of Animal Abroad and Donkey Sanctuary Project Clinic, at Debre Zeit, Ethiopia, from November 2014 to April 2015. The objectives were to describe clinical epidemiology of equine colic, to characterize the main types of equine colic, and to determine the major risk factors associated with equine colic. The method which was used in the study was attending clinical case of equine and assessing physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
7
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 24 publications
5
7
0
5
Order By: Relevance
“…Compaction was the main cause of the diagnosed colic syndrome, with 28.8% of the cases (Table 3). Similar findings were described not only in Brazil (OLIVEIRA et al, 2014), but also in regions of Canada (ABUTARBUSH, CARMALT, SHOEMAKER, 2005), United States (KANEENE et al, 1997), South Africa (VOIGH et al, 2009, and Ethiopia (WORKU et al, 2017), in which the higher occurrence of compaction was explained by anatomical factors, such as decreased lumen of the gastrointestinal tract of horses. As a triggering factor of compaction we can cite the quality of food available to the animals, because in periods of drought the hay is presented with greater amount of lignin (WHITE, 1998), making digestion difficult and favoring accumulation during gastrointestinal transit.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…Compaction was the main cause of the diagnosed colic syndrome, with 28.8% of the cases (Table 3). Similar findings were described not only in Brazil (OLIVEIRA et al, 2014), but also in regions of Canada (ABUTARBUSH, CARMALT, SHOEMAKER, 2005), United States (KANEENE et al, 1997), South Africa (VOIGH et al, 2009, and Ethiopia (WORKU et al, 2017), in which the higher occurrence of compaction was explained by anatomical factors, such as decreased lumen of the gastrointestinal tract of horses. As a triggering factor of compaction we can cite the quality of food available to the animals, because in periods of drought the hay is presented with greater amount of lignin (WHITE, 1998), making digestion difficult and favoring accumulation during gastrointestinal transit.…”
Section: Resultssupporting
confidence: 70%
“…The incidence rate can vary within the same population and is influenced by variables present in and outside the places where the animals are located (ARCHER, PROUDMAN, 2006). In Ethiopia, a rate of 10.3% was found in a 5-month study (WORKU et al, 2017); the annual rate in Iran was 8.6% (MEDNI, MOHAMMED, 2006); and in the Pure Blood training facilities in the British Isles the cumulative colic rate was 5.8% (HILLYER, TAYLOR, FRENCH, 2001). There are several risk factors that influence the development of the colic syndrome, including the increase in dietary concentration, change in housing management (CURTIS et al, 2019), seasonality, gender, age (KANEENE et al, 1997), and racial predisposition (COHEN, GIBBS, WOODS, 1999;TRAUB-DARGATZ et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…management (type and changes of housing and activity), medical history (a previous colic, administration of a medical treatment) and parasite control (the presence of worms and type of deworming program) (13). A prospective study to describe clinical epidemiology of equine colic in the Society for Protection of Animal Abroad and Donkey Sanctuary Project Clinic, at Debre Zeit, Ethiopia, from November 2014 to April 2015, reported that the incidence of colic was 10.3% (14). The incidence of colic in our study was 80% in Arabian horses.…”
Section: Discussionmentioning
confidence: 99%
“…(2/65), in donkeys, horses, and mules, respectively, and the case fatality rate of equine colic was 15.38% (10/65). Statistically, the differences were highly significant (p < 0.01) for the impaction colic in relation to the species (14). Nutrition, and particularly the changes in feeding, is often associated with colic (15).…”
Section: Discussionmentioning
confidence: 99%